2016
DOI: 10.1016/j.ejor.2015.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Spitzer identity, Wiener-Hopf factorization and pricing of discretely monitored exotic options

Abstract: The Wiener-Hopf factorization of a complex function arises in a variety of fields in applied mathematics such as probability, finance, insurance, queuing theory, radio engineering and fluid mechanics. The factorization fully characterizes the distribution of functionals of a random walk or a Lévy process, such as the maximum, the minimum and hitting times. Here we propose a constructive procedure for the computation of the Wiener-Hopf factors, valid for both single and double barriers, based on the combined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…So we propose a new representation of the characteristic function which is algebraically equivalent to all the previous expressions and does not show the discontinuities of Eqs. (10) and (14) for large maturities:…”
Section: 245 25mentioning
confidence: 99%
See 1 more Smart Citation
“…So we propose a new representation of the characteristic function which is algebraically equivalent to all the previous expressions and does not show the discontinuities of Eqs. (10) and (14) for large maturities:…”
Section: 245 25mentioning
confidence: 99%
“…(23e) can be obtained by applying the chain rule to Eq. (14), and the intermediate terms for ∂φ(θ; u, T )/∂σ can be written in terms of those for ∂φ(θ; u, T )/∂ρ, that is…”
Section: Analytical Gradientmentioning
confidence: 99%
“…Oosterlee (2008, 2009) devised the COS method based on the Fouriercosine expansion. The Hilbert transform (King 2009) has also been successfully employed: by Feng and Linetsky (2008) to price barrier options using backward induction in the Fourier space and by Marazzina et al (2012) and Fusai et al (2016) to compute the factorisations required by the Spitzer identities (Spitzer 1956, Kemperman 1963) via the Plemelj-Sokhotsky relations. Feng and Linetsky showed that computing the Hilbert transform with the sinc expansion, as studied by Stenger (1993Stenger ( , 2011, gives errors that reduce exponentially as the number of fast Fourier transform (FFT) grid points increases.…”
Section: Introductionmentioning
confidence: 99%
“…Pricing derivatives, especially exotic options, is a challenging problem in the operations research literature. Fusai et al (2016) provide extensive references for this, as well as for many non-financial applications of the Hilbert transform and the related topics of Wiener-Hopf factorisation and Spitzer identities in insurance, queuing theory, physics, engineering, applied mathematics, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Fusai et al [37] combined this with Spitzer's identity for a general method of pricing discretely monitored exotic options, with an explicit formula for the fixed strike option. However, the method assumes equidistant monitoring windows.…”
Section: Past Pricing Model For Lookbacksmentioning
confidence: 99%